The Call of the Beyond: Music in Antonioni’s Red Desert - Frolova-Walker Marina (Наука телевидения)
This article discusses Michelangelo Antonioni’s use of music in his 1964 film Red Desert (Il deserto rosso). Before Red Desert, Antonioni had avoided the Hollywood convention of the near-continuous musical score, and made only very sparing use of largely diegetic music. Instead of music in any straightforward sense, he used a kind of structured sound-effects score instead. In Red Desert, there is much more music, and in many ways it performs the traditional function of elucidating or enhancing the film’s narrative and symbolic elements. Even so, the content of the music was strikingly original at the time: an abstract electronic score by Vittorio Gelmetti. Close examination reveals Antonioni’s subtle and ambiguous play with the diegetic or non-diegetic role of his music. At the same time, he retains a sound-effects score that begins to take on musical properties, and which also has a significant function in elucidating the narrative. The two scores contribute much to Antonioni’s portrayal of the central character, Giuliana. Much of the critical response to the film took the main theme to be alienation brought on by industrial development, and demoted the story of Giuliana’s mental illness, assuming that she was to be understood as frivolous and trivial as a character. This article presents an alternative reading, drawing on the rich musical evidence that Antonioni did indeed place his plot at the centre of the film, and, contrary to many of the critics, it demonstrates how the music foregrounds the mental state of Giuliana and invites the viewer to view her plight with compassion.